Management of foreign body ingestion and food bolus impaction in children: a retrospective analysis of 675 cases - Antoniou, Dimitris; Christopoulos-Geroulanos, George (The Turkish Journal of Pediatrics, 2011)
Although foreign body ingestion is a common problem in children, there are no clear guidelines regarding the management of ingested foreign bodies. The aim of this study was to evaluate the effectiveness of our protocol in the work-up and management of children with ingested foreign bodies. Between September 2002 and August 2010, a total of 675 children with suspected foreign body ingestion were seen in the emergency department. At initial presentation, the majority of foreign bodies were located in the stomach (n=392, 58.1%) followed by the small intestine (n=221, 32.7%) and esophagus (n=62, 9.2%). Based on our protocol, 84 (12.4%) patients were admitted at initial presentation, and 5 after a 48-hour observation period at home; 61 (9%) required prompt endoscopic removal. Sixty-eight (10.1%) patients returned for endoscopic removal after a four-week observation period, and 3 (0.4%) patients underwent delayed surgery due to complications. The overall success rate of endoscopic retrieval was 96.1%. There were no major complications. The majority of ingested foreign bodies will pass spontaneously and most children can be safely observed at home. Selective endoscopic intervention is the preferable method for the removal of ingested foreign bodies in pediatric patients.